FACTORS FORMING THE IMAGE OF JAPAN IN THE COUNTRIES OF CENTRAL ASIA - Ashinova, Zh.; Hee, Kim Kyoung (Journal of history, 2018)
Today, the Central Asian states are becoming a strategically important region attracting the attention of the world’s major states, depending on their geopolitical and geo-economic characteristics. It is well known that Japan, along with other major powers in the world, shows great interest in this region. In the 21st century, despite the economic internal crisis, Japan is the center of international forces and the world economy, which is a leader in many industries and trade, science and technology. We see that relations between Japan and the countries of Central Asia are developing dynamically. Japan has a high reputation among the countries of Central Asia. It has a positive image as a peace-loving and friendly country that is trying to provide genuine assistance to developing countries. Today Japan is one of the key donors in the Central Asian region. This article examines the image of Japan in the countries of Central Asia and the key factors that influence the formation of the image of the state in this region. Among them, Assistance in ODA and using of soft power are the main prerequisites.